Health Equity and Enrollment in Preventive Parenting Programs: A Qualitative Study of Filipino Parents. Issue 2 (3rd April 2022) - Javier, Joyce R.; Deavenport-Saman, Alexis; Florendo, Ellynore; Bantol, Kamil Evy A.; Palinkas, Lawrence A.
ABSTRACT: This qualitative study identified the parent health beliefs and normative beliefs related to child behavioral and mental health problems and examined the benefits and barriers of enrolling in an evidence-based parenting intervention among Filipino parents of school-aged children. A secondary aim was to also use the results to inform the development of a theory-based video intervention to increase enrollment in parenting interventions. Semi-structured interviews were conducted with fifteen parents who had or had not participated in the Incredible Years® parenting program, an evidence-based parenting intervention. Interviews were recorded and transcribed verbatim. Using a "Coding Consensus, Co-occurrence, and Comparison" methodology, emergent themes were mapped into a matrix against a priori-coded health belief model (HBM) and Theory of Planned Behavior (TPB) constructs. Parents believed that perceived susceptibility could be influenced by including knowledge of health disparities affecting Filipino youth in the U.S. Perceived severity was related to behavioral and mental health concerns about school, family dynamics, bullying and parent coping strategies. Perceived benefits included strengthening parent-child relationships, creating support systems, and learning positive parenting skills. Perceived barriers included logistics, stigma, and the perception of the relevance of the program, cultural factors such as generational differences about parenting, and family issues. Social norms and subjective norms related to parent participation were also discussed. Applying the HBM and TPB to enrollment in parenting interventions may explain low enrollment rates. Future interventions need to target perceived susceptibility to future behavioral health problems, barriers, and benefits to enrollment, and influence subjective and social norms.